Negative reciprocity and the interaction of emotions and fairness norms - Ernesto Reuben; Frans van Winden (Center for Economic Studies and ifo Institute (CESifo), 2006)
This experimental study investigates how behavior changes after punishment for an unkind action. It also studies how fairness perceptions affect the reaction to punishment and whether this effect is consistent across repeated play and role experiences. A repeated version of the power-to-take game is used. In this game, the proposer can make a claim on the resources of a responder. Then, the responder can destroy any part of her own resources. The focus is on how proposers adjust their behavior depending on their fairness perceptions, their experienced emotions, and their interaction with responders. We find that fairness plays an important role in the behavior of proposers. Specifically, deviations from a perceived fairness norm trigger feelings of shame and guilt, which induce proposers to lower their claims. However, we also find that the perceived fairness norm varies considerably between individuals. Therefore, it is not the case that proposers who considered they were acting fairly were particularly nice to responders. Our results also show that the different types of individuals predicted by models of social preferences, can be traced among the subjects that played the same role in both periods, but fail to describe the behavior of subjects who switched from one role to the other.
Keywords: C90; Z13; D01; 330; Gerechtigkeit; Emotion; Soziale Norm; Experiment; Verhaltensökonomik